Correlates of Meeting the Muscle-Strengthening Exercise Guidelines in Children and Adolescent - Gu, Jiayi; Hong, Jin-Tao; Lin, Youliang; Yan, Jin; Chen, Sitong (Frontiers in Public Health, 2022)
This study aimed to explore the potential correlates of muscle-strengthening exercise (MSE) in Chinese children and adolescents. A convenient sample (n = 3733) was recruited into this study. Self-reported questionnaires were used to collect information on sex, grade, ethnicity, residence, family composition, moderate to vigorous physical activity (MVPA), family income, parent’s education level and MSE in children and adolescents as well as their parent(s). The prevalence of meeting the MSE guidelines was 62.1%. Children and adolescents who were in primary or middle school were more likely to meet the MSE guidelines ([primary school] OR = 2.33, 95% CI: 1.16-4.68; [middle school] OR = 4.62, 95% CI: 2.27-9.39). Children and adolescents with Han ethnicity had a higher likelihood to meet the MSE guidelines (OR = 1.97, 95% CI: 1.37-2.83). Children and adolescents meeting the MVPA recommendation were more likely to meet the MSE guidelines (OR = 5.41, 95% CI: 3.97-7.37). Relative to those who had a parent not meeting the MSE guidelines, those with either father or mother meeting the MSE guidelines were more likely to meet the MSE guidelines (OR = 1.32, 95% CI: 1.13-1.55). Our study may offer evidence for future MSE interventions in Chinese children and adolescents.